A Rare Coexistence of Klippel–Trenaunay Syndrome and Cardiac Sarcoidosis - Shriya Sharma; Aarti Desai; Hans Mautong; Patricia Mergo; Juan Leoni; Jose Ruiz; Rohan Goswami (Biomedicines, 2025)
Klippel–Trenaunay (KT) syndrome and Cardiac Sarcoidosis (CS) are two distinct medical conditions that rarely coexist, each presenting unique challenges in diagnosis and management. Here, we present a rare case of a 30-year-old male with a history of KT syndrome complicated by recurrent deep vein thrombosis, who presented with symptoms of acute heart failure including shortness of breath, fatigue, dizziness, palpitations, and chest pain and was subsequently diagnosed with isolated CS. We discuss the importance of thorough clinical evaluation and multimodal diagnostic approaches in this complex scenario with overlapping symptoms and diagnostic dilemmas.